Tabayyun sebagai Strategi Literasi Digital dalam Mengatasi Kecemasan Psikologis tentang Uji Coba Vaksin Bill Gates di Indonesia - Fitri Ramadhani; Konto Iskandar Dinata (Al-Kindi, 2025)
This article discusses the importance of applying the principle of tabayyun based on the values of ushuluddin and the approach of Islamic psychology in responding to the contemporary digital information flow, particularly in the case study of Bill Gates’ vaccine trial in Indonesia. This study aims to examine how the values of tauhid, ‘adl, amanah, and hisbah are effective in overcoming psychological anxiety caused by exposure to misleading information and in countering hoaxes. Furthermore, psychological concepts such as tazkiyatun nafs, qalbun salim, muhasabah, sabar, and syukur play a role in building critical attitudes, mental health, and ethics in receiving and disseminating information. The research method used is qualitative with a library research type, involving the collection and analysis of data from various literature sources such as scientific journals, articles, and official documents from government and related institutions. Descriptive and critical analysis are applied to produce a comprehensive understanding of the synergy between spiritual and psychological values in facing information challenges in the digital era. The results show that the integration of ushuluddin values and Islamic psychology through tabayyun is effective in overcoming psychological anxiety caused by exposure to misleading information and in countering hoaxes.